Relationships between morphological features of inflorescence and capsule borer incidence in castor: Relationships between morphological features of inflorescence and capsule borer incidence in castor - R SATHISHKUMAR; P DURAIMURUGAN; T MANJUNATHA; S SENTHILVEL (Journal of Oilseeds Research, 2023)
The association of morphological features of inflorescence viz., presence/absence of spine on the capsule, presence/absence of bloom and compactness on the incidence of capsule borer was studied in breeding populations segregating for these traits. The spine and bloom on capsules were significantly correlated with per cent capsule damage whereas weak correlation was observed between spike compactness and pest incidence. Castor genotypes with non-spiny capsules and less or no bloom are expected to be less prone to capsule borer damage.